Comida e poder: análise histórica da Campanha Nacional de Alimentação Escolar no Ceará (1964- 1972) - Aragão, Francisco José Alves de (2016)
This research had as object of study the CNAE - Campanha Nacional de Alimentação Escolar (National Campaign of School Nourishment), in Ceará State, between 1964 and 1972. This period corresponds to the managing administrations of the doctor Pedro Almino de Queiroz e Souza (Federal Representative of the Campaign, at state level/CE) and the veterinarian/general of the army reserve José Pinto Sombra (Campaign Superintendent, at national level). The aim of the research was to assess the Campaign historically and critically, with a purpose of undertaking an interpretation that would fulfill this historiographic lack, such as the ones that exist related to the History of School Nourishment in Brazil, in snips more delimited of time and space. The historical sources related to the object of this research were speeches from newspapers of that period (968 newspapers reports) and the speech/narrative of Pedro Almino de Queiroz e Souza, collected from an interview performed on April 2016 (Oral History). The interview was open and with a semi structured script, with few questions based on the general issues of the research, and on the ones that emerged from the initial analysis of the journalistic data. This interview was first recorded and transcribed afterwards. From a methodological and cross-curricular plurality individualized according to the characteristics of the research, we take as theoretical methodological basis the fundaments of Analysis of Speech; the New History (Nouvelle histoire); the Content Analysis, and lastly, the Oral History. The Critic Theory was elected as theoretical analytical basis. The Content Analysis undertaken from the newspapers identified three thematic dimensions as to CNAE in Ceará (between 1964 and 1972): 1) speeches about the functional administrative dynamic of the Campaign; 2) speeches about the pedagogical dynamic of the Campaign, and 3) speeches about the political ideological dynamic of the Campaign. Thus, we could go over and confirm that CNAE in Ceará State, in the period analyzed, did not deviate the rules of public policies conduct of that historical moment, reproducing practices and speeches that aimed to legitimate those militaries government, harshly technocrat, and, managing the state agencies with strict control, aimed, actually, to dominate the society. Pari passu, actions to the formation of a future consuming market were implemented, and to the installation of foodstuff industry all over the country. Eventually, this research intended to contribute to the approximation of the Education to the debate/dialogue cross-curricular that marks this field of knowledge, once any scientific discipline embodies completely the phenomenon of nourishment and eating sociability. The insertion of the nourish thematic in the educational researches is plenty salutary, whereas there is not systematic discussion about the matter, being most of the researches undertaken through a biological/nutritional bias and developed by food engineers, nutritionist and doctors, what makes clear the disinterest of educators and historians for such significant study.